2018
DOI: 10.1371/journal.pone.0194651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasonographic features of male breast tumors: A retrospective analysis

Abstract: ObjectiveThe purpose of this study was to determine clinical and ultrasonographic characteristics of male breast tumors.MethodsThe medical records of male patients with breast lesions were retrieved from an electronic medical record database and a pathology database and retrospectively reviewed. A total of 112 men (125 breast masses) with preoperative breast ultrasonography (US) were included (median age, 59.50 years; age range, 15–96 years). Data extracted included patient age, if the lesions were bilateral, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Due to the low abundance of breast tissue, mammography can be difficult to perform in the male subject [ 17 ]. Some studies have even found that ultrasound and clinical examination may be enough to decide what to do with a breast lesion in the male subject [ 18 ]. In Africa, there are a few studies on the radiopathological correlation of lesions suspected of breast cancer in men, such as that of N'timon et al [ 19 ] in Togo and Ouedraogo et al [ 20 ] in Burkina Faso.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the low abundance of breast tissue, mammography can be difficult to perform in the male subject [ 17 ]. Some studies have even found that ultrasound and clinical examination may be enough to decide what to do with a breast lesion in the male subject [ 18 ]. In Africa, there are a few studies on the radiopathological correlation of lesions suspected of breast cancer in men, such as that of N'timon et al [ 19 ] in Togo and Ouedraogo et al [ 20 ] in Burkina Faso.…”
Section: Discussionmentioning
confidence: 99%
“…This must also be taken into account in men, where the risk of error seems higher, which can lead to misunderstanding a malignant lesion for a simple gynecomastia due to the high prevalence of these types of lesion in men. In all cases, a unilateral gynecomastia in an elderly subject, in the absence of any hormonal or metabolic factor, must be verified by an ultrasound and a mammography and in case of doubt submitted for fine needle aspiration for cytology or surgical biopsy for histological diagnosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of microcalcifications is lower than female breast cancer. Retroareolar, non-parallel, hypoechoic mass with irregular borders and variable vascularity are well-known Accompanying secondary findings can also be seen in US [3,4,7,9,15] (Fig. 11).…”
Section: Malign Breast Lesions Invasive Ductal Carcinoma (Idc)mentioning
confidence: 95%
“…However, parenchymal opacity or distortion may, also, be seen if invasive carcinoma accompanies. The findings on US are non-specific, but coexistent IDC foci may be seen as mass or distortion [6,7,9].…”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%
See 1 more Smart Citation